Cancer Registration and its Role in Cancer Epidemiology - Shin, Hai-Rim (Indonesian Journal of Cancer, 2009)
https://www.scribd.com/doc/45478072/Cancer-Registration-and-its-Role-in-Cancer-Epidemiology